2018
DOI: 10.1111/1365-2656.12789
|View full text |Cite
|
Sign up to set email alerts
|

Decreases in beetle body size linked to climate change and warming temperatures

Abstract: Body size is a fundamental ecological trait and is correlated with population dynamics, community structure and function, and ecosystem fluxes. Laboratory data from broad taxonomic groups suggest that a widespread response to a warming world may be an overall decrease in organism body size. However, given the myriad of biotic and abiotic factors that can also influence organism body size in the wild, it is unclear whether results from these laboratory assays hold in nature. Here we use datasets spanning 30 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
87
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(91 citation statements)
references
References 61 publications
3
87
1
Order By: Relevance
“…Such a phenotypic trait, for example, could be body size. Body size is a quantitative trait fundamental to life‐history theory and population dynamics (Gibert, Allen, Hruska, & DeLong, ; Pigeon, Ezard, Festa‐Bianchet, Coltman, & Pelletier, ), which has been shown to decline in response to decreases in resource availability (Clements & Ozgul, ), increases in temperature (Forster, Hirst, & Atkinson, , ; Gardner, Peters, Kearney, Joseph, & Heinsohn, ; Tseng et al, ) and increases in harvest rate (Clements et al, ). In our model, the optimum environmental change will affect the dynamics of the phenotype.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a phenotypic trait, for example, could be body size. Body size is a quantitative trait fundamental to life‐history theory and population dynamics (Gibert, Allen, Hruska, & DeLong, ; Pigeon, Ezard, Festa‐Bianchet, Coltman, & Pelletier, ), which has been shown to decline in response to decreases in resource availability (Clements & Ozgul, ), increases in temperature (Forster, Hirst, & Atkinson, , ; Gardner, Peters, Kearney, Joseph, & Heinsohn, ; Tseng et al, ) and increases in harvest rate (Clements et al, ). In our model, the optimum environmental change will affect the dynamics of the phenotype.…”
Section: Methodsmentioning
confidence: 99%
“…To evaluate the efficacy of trait-based EWS (Clements & Ozgul, 2016), information from mean phenotype z was incorporated with the leading indicators in an additive manner. We z-standardized the , which has been shown to decline in response to decreases in resource availability (Clements & Ozgul, 2016), increases in temperature (Forster, Hirst, & Atkinson, 2011Gardner, Peters, Kearney, Joseph, & Heinsohn, 2011;Tseng et al, 2018) and increases in harvest rate (Clements et al, 2017). In our model, the optimum environmental change will affect the dynamics of the phenotype.…”
Section: Trait-based Ewsmentioning
confidence: 99%
“…Ecological rules such as the temperature-size rule (TSR) and Bergmann's rule (latitude-size clines) have led to the prediction that body size declines will be a "universal" response to climate change (Daufresne, Lengfellner, & Sommer, 2009;Gardner, Peters, Kearney, Joseph, & Heinsohn, 2011). Specifically, the TSR predicts that individuals developing in cool conditions will be larger as adults than those developing in warm conditions, and this has been shown to be the case for many species (Daufresne et al, 2009;Gardner et al, 2011;Ghosh, Testa, & Shingleton, 2013;Horne et al, 2015;Irie, Morimoto, & Fischer, 2013;Ohlberger, 2013;Sheridan & Bickford, 2011;Tseng et al, 2018). However, it has also recently been shown that some species increase in size with increasing temperature, whereas some species appear to show no temperature-size response (Classen, Steffan-Dewenter, Kindeketa, & Peters, 2017;Fenberg, Self, Stewart, Wilson, & Brooks, 2016;Horne et al, 2015;Høye, Hammel, Fuchs, & Toft, 2009;Scriber, Elliot, Maher, McGuire, & Niblack, 2014;Shelomi, 2012;Upton, Price, Percy, & Brooks, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…With gradual environmental change, the phenotype of a species generally has to evolve in step with the movement of the centre of the carrying capacity, because otherwise the carrying capacity of that species will fall to very low values, making the environment inviable for that species. Such effects can be observed in various populations (Gienapp et al 2008;Baym et al 2016;Tseng et al 2018). For example, numerous studies indicated a global tendency of various species to decrease in body size in warming environments (Guillemain et al 2005;Y.…”
Section: Discussionmentioning
confidence: 91%
“…Body size is an important physiological characteristic that strongly influences metabolism and thermoregulation. For example, decreased body-size due to changing temperature regimes was observed in beetles both in natural and laboratory populations (Tseng et al 2018).…”
Section: Discussionmentioning
confidence: 99%